well the first one is
2 + [3+5(3)]=
2+[18]=20
I' trying to follow the PEMDAS order, but it doesn't seem to always work out.
2 + [3 + 5 (2 + 1) ]=
78.2
3 - 2 * 4 / 2 =
2
6 { 3 + 5 / 2] =
33
9 - 4 (3 + 6 * 2) = __ + 1 =
76
9 - 4 (3 + 6 * 2) =
75
6 + {5 - [2 + (3 - 1) ] } =
7
6 - { 4 - [ 2 - (6 +20) ] } =
30
And then there's something as simple as:
3 - 5 (2 - 4)
I know first, it would be 2 - 4 = -2.
But I'm not sure if I should multiply the parenthesis by BOTH 3 and 5, or just multiply 5 by the parenthesis, THEN subtract that number from 3?
This is where the problem lies. Any help would be great, thanks.
And the next one is
3 - 2 * 4/2 = 3 - 2 * 2 = 2 - 4 = -1
This one's not right, either: 9 - 4 (3 + 6 * 2) =
9 - 4(3 + 12) = 9 - 4(15) = 9 - 60 = -51
And your last one is incorrect: 6 - { 4 - [ 2 - (6 +20) ] } =
6 - { 4 - [ 2 - 26 ] } = 6 - { 4 - [-24] } = 6 - { 4 + 24 } = 6 - 28 = -22
And in this one: 3 - 5 ( 2 - 4 ) = 3 - 5 ( -2 ) = 3 + 10 = 13